EFEKTIVTIAS PEMBELAJARAN DARING PADA PENDIDIKAN VOKASI - Nurhayanti, Ketut (Jurnal Penjaminan Mutu, 2021)
This study aims to describe the effectiveness of online learning in vocational colleges in Hindu theory courses and electrical installation practices. Assessment indicators are student learning outcomes, learning completion, student interests and motivations as well as attractive learning experiences experienced by students during online learning. Quality research with qualitative descriptive research approach is used in this study. Data collection techniques using questionnaires in the form of essays are disseminated through the google form platform and interviews conducted with google meet. Respondents numbered 50 students. The results of online learning research are effective if reviewed from indicators of the value of learning outcomes and complete materials but are not effective if reviewed from behavior changes. Indicators of attractive learning experience will be fun assuming the media used and lecturers can package materials in an interesting, interest and motivational learning students more to the obligation to get value and no other learning alternatives except online.